The Impact of Corporate Governance on the Iranian Banking System Efficiency (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
According to the importance of Corporate Governance and its role in the Banks accountability, transparency and efficiency, the purpose of this study is to investigate the impact of corporate governance on the bank’s efficiency and its relations with banks disclosure of information. Also, this study wants to finds that whether the corporate governance indices can measure the governance conditions precisely? For this purpose, using dynamic panel data model and information of 16 banks of the Iranian banking network during the period of 2007-2017, the relationship between corporate governance indicators and information transparency and their impact on the efficiency of banks have been investigated. The results show that there is no significant relationship between the indicators introduced for corporate governance and information disclosure. Also, none of the indicators introduced for corporate governance had a significant relationship on efficiency of banks, but the information transparency index had a significant positive impact on banks efficiency. According to the results, introduced indices of corporate couldn’t measure the corporate governance situations in the Iranian banking sector.